The impact of emerging technologies and AI on human resources in Singapore - Ng, Sharon Miew Ling (2020)
The technology-driven world coupled by recent developments in future of work brings upon the challenges faced by Singapore organisations in adapting to these changes, particularly in Artificial Intelligence. Over the last few years, technological developments related to Industry 4.0 have created headlines in relation to its impact on the future of work. Although the developments in Artificial Intelligence promises great economic benefits, research has shown the effective application of AI to HR poses different challenges as compared to other areas; the challenges range from functional to theoretical and when data science is applied to decisions about people, it can create severe disputes with what the society deems as crucial for making significant decisions about individuals. This study aims to determine how emerging technologies particularly AI contribute positively to the HR Singapore organisations. Building on existing studies on AI and HR, the study aims to find the effects of AI on organisation and to what extent does AI revolutionise the HR function.